Is eight-plate more effective than reconstruction plate in pediatric guided growth? A systematic review and meta-analysis - Anak Agung Ngurah Krisna Dwipayana; Sherly Desnita Savio; Made Agus Maharjana (Publicaciones Permanyer, 2024)
Introduction and objectives: Pediatric angular deformities in the lower limb need surgeries that are less invasive to correct deformities and prevent premature degenerative changes in the knee. Partial growth arrest, also known as hemiepiphysiodesis, relies on the growth potential of the unaffected side of the physis to facilitate gradual angular correction. Although recognized as an effective implant for this procedure, eight-plate is an expensive device that increases the economic burden for developing countries. There has been some debate about whether a cheaper implant, reconstruction- plate, is comparable in terms of its efficacy in children with angular deformities. Methods: A systematic search was conducted in line with the PRISMA guideline to identify relevant studies through the PubMed, Google Scholar, and Cochrane databases. A total of three studies (181 patients, 339 knees) were included, divided into five meta-analyses, which were processed using Review Manager 5.3. Results: Eight-plate and reconstruction-plate offer comparable efficacy in terms of lateral distal femur angle (LDFA) correction (p = 0.30, I2 = 99%, MD 3.38), medial proximal tibial angle (MPTA) correction (p = 0.27, I2 = 94%, MD 4.39), the implant failure rate (p = 0.28, I2 = 0%, OR 0.36), rebound rate (p = 0.44, I2 = 0%, OR 0.44), and complication rate (p = 0.36, I2 = 0%, OR 0.47). Discussion: Both internal and external factors should be monitored closely in hemiepiphysiodesis, as they may play a role in the success of the surgery. Internal factors include being overweight and physeal conditions. External factors include plate positioning, screw placement, and the screw tightening technique. Regular follow-up should also be given, as this may minimize the risk of overcorrection and the rebound rate. Reconstruction-plate resulted in comparable efficacy to eight-plate in terms of angular correction, implant failure rate, rebound rate, and complication rate.